CORROSION RESISTANCE OF LASER CLADDED NiCrBSi COMPOSITE COATINGS - HULKA, Iosif; ȘERBAN, Viorel-Aurel; UTU, Ion-Dragoș; DUTEANU, Narcis; PASCU, Adrian; ROATĂ, Ionuț Claudiu (Studia Universitatis Babeș-Bolyai Chemia, 2015)
NiCrBSi powders were deposited on medium alloy steel substrate using laser cladding process and electrochemically tested at room temperature by immersing the specimens in 3.5% NaCl solution in order to study their corrosion behavior. The coatings were obtained using different cladding parameters like scanning speed and overlap percentage. Investigations techniques such as scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) measurements were employed to study the microstructure and chemical properties of the coatings. It was found that the microstructural characteristic and corrosion behavior are linked to coatings thickness, dilution and diffusion of Fe within the coating.